Experimental determination of creep fatigue life of 316L stainless steel pipe - Mohammad, Khairul Azhar (2011)
Component of engineering structures operating at high temperature such as jet engine, pressure vessels, nuclear reactors, steam and gas turbine including oil and gas plant are subjected to severe thermal and mechanical loading. One of them is tubular structure which is widely used with extensive usage from domestic to aviation. Thus estimate of life and safety is an essential part of design and use. Since the external surface of structures always in contact with environment and is exposed to weather and crash and also due to imperfection during product fabrication, surface crack may exist. The main purpose of this study was to characterize and examine the relative importance of the mechanisms of creep-fatigue interaction on fatigue life in cylindrical structure at high temperature. Fatigue tests were carried out with constant amplitude at room temperature and at high temperature for smooth specimen in the finite life region of material. Meanwhile constant load and high temperature as 565oC will be imposed to specimen for creep test. The nature of the hold period (tensile or compressive) affects fatigue life and the surface crack patterns. Creep-fatigue tests with five minutes holds time at maximum tensile stress were conducted using hourglass specimen “Type 316L stainless steel” at temperatures of 565oC. Optical and scanning electron microscopy will be carried out to characterize metallurgical damage in the understanding of microscopic damage mechanics. The fatigue behaviors of 316L stainless steel from experimental revealed superior behavior compared to as predicted model but still show good agreement with the model. The variation of creep strain rates is clearly show that the secondary creep obeyed with a power of law relationship as constant increase creep rate till the tertiary stages. Experimental results from high temperature low cycle fatigue test show by increasing the temperature there is a reduction in fatigue life of the material. It reduces the fatigue strength of the material. Therefore, the combination of temperature and loading fatigue serve more damage and life reduction in component. It was also determined that crack initiation and propagation at grain boundaries was accelerated under creep fatigue loading condition. It was found that crack initiation occupied a major portion of the failure life under fatigue and creep-fatigue. Creep failure mechanism predominates after short times (>5 minutes). Finally, the optical and SEM microscope were employed to capture better picture the quality of microstructure and macrostructure of fracture surface, with tensile hold was caused mixed transgranular (TG) + intergranular (IG) propagation. Crack initiation was also changed to IG by employing a tensile hold which was otherwise TG.